Hubungan Insomnia Terhadap Tekanan Darah Pada Lansia - Bangun Dwi Hardika; Vincencius Surani; Lilik Pranata (Journal of Educational Innovation and Public Health, 2023)
The increasing number of elderly people will have an impact on all arrangements in the community or family. Problems that often occur in the elderly will be a burden on the elderly, one of the problems that occur is insomnia. So this study aims to find out the relationship between insomnia and blood pressure in the elderly. Research method with quantitative survey analysis design, crossectional. The research was conducted in a nursing home with a sample size of 30 active elderly respondents with insomnia disorders. The results showed that there was no relationship between the level of insomnia and blood pressure with a significance value of 0.757> p value 0.05. These results indicate that statistically there is no relationship between the elderly with insomnia and blood pressure. Suggestions for home managers to provide interventions for elderly people who experience insomnia disorders with light therapy that is fun and has a positive impact on the elderly..